Kajian Kuantitas dan Karakteristik Cairan Pulpa Hasil Samping Fermentasi Biji Kakao Menggunakan Wadah Sistem “Termos” Sebagai Bahan Baku Asam Asetat - Ganda Putra, Gusti Putu; Wartini, Ni Made (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 1, No. 1, 2014, 2015)
The application of cocoa fermentation methods using fermentation container of "thermos" system allows watery sweatings byproduct of the pulp of cocoa beans can be accommodated. The purpose of this study were: 1) to study the effect of using fermentation container of thermos system for the quantity and characteristics of the watery sweatings byproduct of the pulp of cocoa beans during fermentation 2) get the watery sweatings byproduct of the pulp of cocoa beans as a potential feedstock of acetic acid.This study used a factorial BRD with 2 factors. The first factor is the container material type of fermentation of "thermos" system which consists of three types, namely: wood, plastic, and a single container (control) and the second factor is the time of fermentation consists of 6 levels, namely: 1, 2, 3, 4, 5 and 6 days. Each treatment combination (18 combinations) was made in 2 groups to obtain 36 experiment units. Observations made include: the temperature in the pile of cocoa beans, the quantity (% w/w), pH, and total acid (meq NaOH/g).The results show that: 1) the use of container material type of fermentation of "thermos" system and the fermentation time affect temperatures in the piles of cocoa beans and characteristics such as: quantity, pH, and total acid content of watery sweating byproduct produced during fermentation of cocoa beans and 2) fermentation container of "thermos" system of wood with a time of ferment 1-2 days to produce a watery sweating byproduct of the fermented cocoa beans as a potential feedstock of acetic acid. Key words: cocoa, fermentation, watery sweatings, acetic acid